Developing a Medical School Curriculum for Psychological, Moral, and Spiritual Wellness: Student and Faculty Perspectives - Mitchell, Christine M. (J Pain Symptom Manage, 2016)
CONTEXT: Although many studies have addressed the integration of a religion and/or spirituality curriculum into medical school training, few describe the process of curriculum development based on qualitative data from students and faculty. OBJECTIVES: The aim of this study is to explore the perspectives of medical students and chaplaincy trainees regarding the development of a curriculum to facilitate reflection on moral and spiritual dimensions of caring for the critically ill and to train students in self-care practices that promote professionalism. METHODS: Research staff conducted semiscripted and one-on-one interviews and focus groups. Respondents also completed a short and self-reported demographic questionnaire. Participants included 44 students and faculty members from Harvard Medical School and Harvard Divinity School, specifically senior medical students and divinity school students who have undergone chaplaincy training. RESULTS: Two major qualitative themes emerged: curriculum format and curriculum content. Inter-rater reliability was high (kappa = 0.75). With regard to curriculum format, most participants supported the curriculum being longitudinal, elective, and experiential. With regard to curriculum content, five subthemes emerged: personal religious and/or spiritual (R/S) growth, professional integration of R/S values, addressing patient needs, structural and/or institutional dynamics within the health care system, and controversial social issues. CONCLUSION: Qualitative findings of this study suggest that development of a future medical school curriculum on R/S and wellness should be elective, longitudinal, and experiential and should focus on the impact and integration of R/S values and self-care practices within self, care for patients, and the medical team. Future research is necessary to study the efficacy of these curricula once implemented.